Characterization of Salmonella enterica isolated from street food and clinical samples in Malaysia - Robin, Tunung; Chai, Lay Ching; Ragavan, Usha Menon; Lee, Hai Yen; Abu Bakar, Fatimah; Mohamad Ghazali, Farinazleen; Radu, Son (Universiti Putra Malaysia Press, 2007)
Salmonella enterica is one of the major causes of bacterial foodborne infection. The aims of this study were to determine the antibiotic resistance and the genetic diversity of Salmonella enterica isolated from street foods and clinical samples and to understand the correlation between the prevalence of serovars and genotypes with their source (street food and clinical samples) and geographic origin (Negeri Sembilan, Malacca and Selangor in Peninsular Malaysia). The enterobacterial repetitive intergenic consensus (ERIC) PCR analysis distinguished the Salmonella isolates into 19 ERIC types, with one untypable isolate. Dendrograms were specifically constructed for the S. Biafra and S. Typhi isolates. Identical or very similar ERIC types among the S. Biafra isolates from street food samples indicate transmission of the S. Biafra among the street foods, as well as possible cross-contamination of the street foods. In addition, the identical or very similar ERIC types among the S. Typhi isolates from human samples examined suggest possible similarity in their source of infection. All the twenty four isolates were resistant to rifampin and none were resistant to cefuroxime. Most isolates displayed multiple resistances. Dendrogram of antibiotic resistances produced six clusters, with similarity levels between 18.8% and 100%. Generally, street food and clinical isolates tend to cluster apart. Dendrogram to cluster the antibiotic groups showed that they could be grouped according to classes based on mode of inhibition. The findings suggest that street food contaminated with drug-resistant Salmonella enterica can be an important factor in the continuous emergence of antibiotic resistant Salmonella enterica.